Project Based Learning Pedagogical Design in STEAM Art Education - Mohd Hawari, Ahmad Dasuki; Mohd Noor, Azlin Iryani (Universiti Teknologi MARA, 2020)
This paper explores the potential of Project-Based Learning (PBL) approach in a multidisciplinary art classroom involving STEAM (Science, Technology, Engineering, Art, and Mathematics) education. The PBL approach involves a dynamic classroom approach, which emphasises on long-term learning, interdisciplinary and student-centred art activities. This implementation would benefit the teaching strategies in art projects; helping students understand lessons, improving communication and soft skills, as well as enhancing leadership skills and creativity. However, there are some concerns related to the PBL approach: i) difficulties in finding appropriate teaching strategies, ii) choosing suitable projects, iii) selecting relevant measurement tools or assessing rubrics, and iv) developing learning content to suit the objective and the main purpose of the art curriculum. In identifying this approach’s potential, a study was carried out involving two art teachers in their respective classrooms. Data was collected through interviews, observations, and document analysis of their teaching strategies, which included three main phases of PBL implementation in creating art projects. The findings suggest that the PBL pedagogical design has the ability to improve teaching strategies and with potential to replace a traditional, teacher-led art classroom. The approach is effective in guiding teachers to manoeuvre an authentic art lesson while benefiting the students through emphasis on the artistic process of creating a STEAM project, while focusing on culminating the necessary art content through active collaboration, exploration of real-world challenges and curricular activities’ problem-solving. However, a number of challenges were identified, such as curriculum demand, learning content, teachers’ and students’ attitude, and access to instruments. Hence, a number of suggestions and recommendations are proposed to help resolve the challenges. The implications of the study on arts curriculum, school systems and other higher institutions are also discussed.